Biodiversity of bananas on farms in Uganda - Edmeades, Svetlana; Smale, Melinda; Karamura, Deborah (International Food Policy Research Institute, 2006)
Uganda is among the world’s leading countries in terms of banana production and consumption. Bananas occupy the largest cultivated area among staple food crops in Uganda and are primarily grown on small subsistence farms (plots of less than 0.5 ha). In addition to being a major food staple, bananas are an important source of income, with excess production sold in local markets. Average per capita annual consumption of bananas in Uganda is the highest in the world, estimated at close to 1 kg per person per day.